Floating tones and contour tones in Kenyang - David Odden (LibraryPress@UF, 1988)
Tonal alternations in the Bantu language Kenyang appear on first consideration to be rather complicated but yield to analysis into a small number of rules, which reveal interesting properties of floating tones, contour tones, and the tone-bearing unit in the language. This study focuses on the following problems. First, there is a phonetic contrast, found only at the end of the utterance, between the downgliding L of eket and the unreleased L of basemo. Unreleased L will be shown to derive from rising tone. Second, I argue that syllable final consonants may be tone-bearing, a claim supported by analysis of tone alternations resulting from postlexical resyllabification. Third, Kenyang uses floating L prefixes to form morphological verb tense distinctions. There is a behavioral contrast between the free L tone marking the progressive, which triggers downstep and blocks a spreading rule, versus the free L used in the recent past, which docks to the first root vowel, thereby causing the root tone to shift rightward. The analytic problem is to find a way to represent these two types of floating L. The distinction can be handled by assigning them to different levels of the lexical phonology, so that the shift-inducing L is added when verb roots are inserted, but the float-only L is added at a later stratum-. Finally, I show that the interaction between the two rules H Spreading and Fall Simplification provides evidence for the cyclic application of postlexical rules.